The Ideology of Patronage and the Question of Identity in the Early Dādūpanth - Zapart, Jarosław (Religions, 2022)
This article focuses on the Dādūpanth, a religious community centered on the teachings of Dādū Dayāl (1544-1603), a Sant poet of Rajasthan. The aim of the text is to analyze how various forms of patronage affected the formation of the ideology and identity of this community. The article examines especially the Dādūpanthī ideology of patronage by focusing on the Dādū Janma Līlā (c. 1620), which contains an account of the supposed meeting between Dādū and the emperor Akbar, during which Dādū rejects all offers of patronage. His position needs elucidation as it stands in contrast with the later tendency of the post-17th century Dādūpanth to accept royal and merchant patronage. After analyzing how the hagiography establishes Dādū’s authority and having considered in what types of manuscripts the hagiography was distributed by itinerant preachers, it is suggested that this work is driven by a strong proselytic agenda and that it employs a ‘pedagogical strategy’—represented by the topos of rejected royal support—to establish relationships with merchant patrons. The article concludes with the observation that the increase in royal patronage from the 17th to the 19th century led to changes in the Dādūpanthī ideology that entailed a shift toward a Vaishnava identity.